Preparation method of rare earth and noble metal double-doped zinc oxide-based photocatalyst material
Through rare earth and precious metal double-doped zinc oxide-based photocatalyst materials, the problem of insufficient catalytic activity of existing photocatalysts under visible and low-light conditions is solved, more efficient formaldehyde removal and bacterial killing are achieved, and the spectral response range is expanded and the spectrum is improved. The utilization rate of light sources.
Patent Information
- Application Number
- CN202411430852.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing photocatalytic activity of the photocatalytic materials under visible and low light conditions is insufficient, making it difficult to effectively remove formaldehyde and kill bacteria, and have a limited range of spectral response to the spectrum.
Using rare earth and precious metal double-doped zinc oxide-based photocatalyst materials, increase oxygen vacancy through rare earth element doping, and continue to fill light with rare earth long-term luminescent powder. Physical doping of precious metals reduces electron-hole recombination rate, and improves photocatalytic reaction activity and efficiency. , expand the spectral response range.
It significantly improves the reactivity and efficiency of photocatalysts, enhances the removal and killing ability of formaldehyde and bacteria, improves the utilization rate of light sources, and adapts to visible and low-light light sources.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalyst materials and preparation thereof, and in particular to a method for preparing a rare earth and noble metal dual-doped zinc oxide-based photocatalyst material. Background Art
[0002] Photocatalyst technology is a technology that uses light energy to carry out catalytic reactions. It can be specifically divided into ultraviolet type and visible light type. When nano-photocatalysts are irradiated with light, the valence band electrons are excited to the conduction band, forming electrons and holes, which react with O2 and H2O adsorbed on their surfaces to generate superoxide anion free radicals, O 2- And hydroxyl radical -OH, its free radical has a strong oxidative decomposition ability, which can destroy CC bond, CH bond, CN bond, CO bond, OH bond, NH bond in organic matter, decompose organic matter into carbon dioxide and water; at the same time, it destroys the cell membrane of bacteria and solidifies the protein of viruses, changes the living environment of bacteria and viruses, and kills bacteria and viruses. In daily life, photocatalysts can effectively degrade toxic and harmful gases in the air such as formaldehyde and purify the air; at the same time, it can effectively kill a variety of bacteria, and decompose and harmlessly treat toxins released by bacteria or fungi. In addition, photocatalysts are also used for indoor pollution prevention and control, such as removing mites and eliminating odors.
[0003] The photocatalyst materials that have been studied include TiO2, ZnO, CdS, WO3, Fe2O3, PbS, SnO3, In2O3, ZnS, SrTiO3 and SiO2. These semiconductor oxides have certain photocatalytic activity in degrading organic matter and are stable and non-toxic. Because most of them are prone to chemical or photochemical corrosion, they may not be suitable as universal photocatalysts. The photocatalysts usually mentioned are mainly nano-titanium dioxide, but zinc oxide photocatalysts are also widely used.
[0004] But zinc oxide is more active than titanium dioxide. Zinc oxide is a direct bandgap semiconductor, and titanium dioxide is an indirect bandgap semiconductor. In direct bandgap semiconductors, electrons can jump directly from the valence band to the conduction band without the assistance of phonons. In indirect bandgap semiconductors, the transition of electrons requires the participation of phonons, which leads to energy loss and reduced efficiency. Therefore, the electron transition speed of zinc oxide is very fast, and electrons can quickly move from the conduction band to the valence band. The transition speed of titanium dioxide electrons is much slower, and more energy is required to excite electrons to the valence band.
[0005] Comparative Document 1: On October 31, 2016, China Powder Technology Network published a product introduction material called Nano TiO2 / Diatomite Composite Photocatalytic Technology. The official account URL is https: / / mp.weixin.qq.com / s / pytKTqvEdZuj_yCmXu208w. This technology uses diatomite as raw material, integrates nano TiO2 precipitation loading and temperature-controlled calcination crystallization technology to develop a composite environmentally friendly new material with natural diatomite as carrier and nano titanium dioxide as catalytic active component. The formaldehyde removal rate within 24 hours under fluorescent light is ≥80%, and it has excellent adsorption and capture functions and photocatalytic degradation functions. It can continuously and efficiently adsorb and degrade indoor air pollutants such as formaldehyde and toluene and pollutants in water.
[0006] Comparative document 2, Chinese invention patent 202011065283X, a visible light responsive photocatalyst composite material and its preparation method, the photocatalyst composite material is prepared by physically mixing rutile nano-titanium dioxide, copper-doped nano-zinc oxide (pre-synthesized), nano-silver, graphene, natural plant extracts, formaldehyde scavengers, additives, dispersants, deionized water, etc., and the formaldehyde removal rate is as high as 96.1%.
[0007] However, the formaldehyde removal rate of the nano-TiO2 / diatomaceous earth composite photocatalyst in the above-mentioned comparative document 1 under sunlight is only 80%. In comparative document 2, although the formaldehyde removal rate is as high as 96.1%, the addition of natural plant extracts, formaldehyde capture agents and other rapid formaldehyde removal factors cannot fully reflect the performance of the original photocatalyst material.
[0008] The rare earth and noble metal doped zinc oxide-based photocatalyst material responsive to visible light and weak light sources of the present invention has a primary particle size of less than 50 nm and a light absorption rate of 0.6 to 0.8 at a wavelength of 570 nm measured by diffuse reflectance spectroscopy, indicating that the material can effectively absorb light energy and has a strong photocatalytic ability, thereby promoting the occurrence of photocatalytic reactions. The preparation method improves the reactivity and efficiency of the photocatalyst by co-doping with rare earth elements to increase oxygen vacancies, supplementing light in the dark with rare earth long-acting luminous powder to continue the photocatalytic properties, and physically doping with noble metals to reduce the recombination rate of electron-hole pairs, thereby expanding the response range of the photocatalyst to the spectrum, thereby better adapting to visible light and weak light sources, increasing the utilization rate of the light source, and having a stronger removal and killing effect on formaldehyde, VOCs, and bacteria and viruses. Summary of the invention
[0009] A method for preparing a rare earth and noble metal dual-doped zinc oxide-based photocatalyst material, the specific steps are as follows:
[0010] 1. Mix the soluble compounds of zinc and rare earth into a uniform solution, then add the combined complexing agent and heat to form a golden and transparent zinc and rare earth eutectic viscous liquid;
[0011] 2. Place the zinc and rare earth eutectic viscous liquid in a 250°C oven and heat for 8 hours to prepare a black precursor;
[0012] 3. Place the black precursor in a muffle furnace and calcine at 450-800°C for 3-12 hours to prepare rare earth element-doped zinc oxide;
[0013] 4. Rare earth element-doped zinc oxide, rare earth long-lasting luminous powder, dispersant and deionized water are prepared into a nano-scale composite dispersion in a nano-sand mill, and the average particle size is controlled within 50 nm;
[0014] 5. Add noble metal nitrate or chloride to the nano-scale composite dispersion, fully dissolve it, then add grafted carboxyl starch, shear to form a stable composite solution, and filter it repeatedly through a filtration system until the filtered clear liquid no longer contains noble metal ions, thereby obtaining a composite material filter cake coated with noble metal ions;
[0015] 6. The composite material filter cake coated with precious metal ions is decomposed at 500°C or reduced at 200-300°C by 5% hydrogen-argon mixed gas to form a rare earth and precious metal doped zinc oxide-based photocatalyst material in which precious metals are uniformly deposited on the surface of rare earth / rare earth element doped zinc oxide photocatalyst.
[0016] Preferably, the zinc soluble compound in step 1 is one of zinc chloride and zinc nitrate; the soluble compound of rare earth is a nitrate of rare earth; the combined complexing agent is a mixture of ethylenediaminetetraacetic acid and citric acid in a mass ratio of 2:1; the rare earth type is one or more of lanthanide elements, scandium and yttrium elements, wherein the lanthanide elements include lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium; the molar ratio of the zinc soluble compound to the rare earth soluble compound is 1:(0.01-0.33), and the mass ratio of the sum of the soluble compound and the rare earth soluble compound to the combined complexing agent is 1:(0.2-1).
[0017] Preferably, in step 4), the mass ratio of rare earth element-doped zinc oxide to rare earth long-lasting luminous powder, dispersant, and deionized water is controlled to be 1:0.1:0.3:(1-4).
[0018] Preferably, in step 5), the noble metal nitrate or chloride is one or a combination of silver nitrate, platinum nitrate, palladium nitrate, rhodium nitrate, ruthenium nitrate, platinum chloride, palladium chloride, rhodium chloride, and ruthenium chloride; the molar ratio of the noble metal to the zinc in the nanoscale composite dispersion is (0.01-0.1):1; the mass ratio of the grafted carboxyl starch to the nanoscale composite dispersion is (0.01-0.1):1.
[0019] Compared with the prior art, the rare earth and noble metal dual-doped zinc oxide-based photocatalyst material prepared by the method described in the present invention has the following beneficial effects:
[0020] 1) By doping rare earth elements in the hexagonal wurtzite structure of zinc oxide, the intervention of different element radii and valence states makes zinc oxide appear spontaneous and relatively stable oxygen vacancies. In addition, the special outer electron structure of rare earth elements can obtain electrons when the light is strong, while maintaining a certain charge inside to attract cations, which inhibits the recombination of electron-hole pairs, thereby achieving stable photocatalytic response capabilities in the full range of ultraviolet and visible spectra.
[0021] 2) At the same time, the physically doped rare earth long-lasting luminous powder is used as an energy storage material. After being irradiated by natural light, fluorescent light, ultraviolet light, etc., it stores light energy. After the light irradiation stops, it can release the stored energy when the light is weak, emitting light in the visible light band, which can maintain the photocatalytic properties of rare earth and precious metal dual-doped zinc oxide-based photocatalyst materials and better adapt to visible light and weak light sources.
[0022] 3) After the noble metal is deposited on the surface of the photocatalyst, it forms physical doping with the rare earth-doped zinc oxide-based photocatalyst material, which can change the electron distribution of the photocatalyst material and affect its surface properties, thereby improving the photocatalytic performance of the material. As an attacher of photogenerated electrons, the noble metal promotes the carrier transport at the interface of the composite system, so that the photogenerated electrons accumulate on the surface of the noble metal, while the holes remain on the surface of the rare earth-doped zinc oxide photocatalyst, effectively reducing the recombination rate of electron-hole pairs and greatly improving the reaction activity of the photocatalyst. In addition, the deposition of noble metals can also change the energy band structure of rare earth-doped zinc oxide, making it more conducive to absorbing low-energy photons and improving the utilization rate of light sources. Specifically, after the noble metal is deposited on the rare earth-doped zinc oxide, electrons will continuously migrate from the rare earth-doped zinc oxide to the noble metal, forming a short-circuited microbattery with rare earth-doped zinc oxide and noble metal as electrodes. The hole pairs generated by the rare earth-doped zinc oxide electrode oxidize the pollutants, while the electrons flow to the noble metal electrode, thereby reducing the recombination rate of electron-hole pairs and improving the reaction activity of the catalyst. This mechanism not only improves the photocatalytic efficiency, but also expands the spectral response range of the photocatalyst, thereby increasing the utilization rate of the light source. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0024] Figure 1 This is a SEM image of zinc oxide doped with rare earth elements in Example 1 of the present invention.
[0025] Figure 2 The particle size of the nano-scale composite dispersion of Examples 1-4 of the present invention varies with the grinding time.
[0026] Figure 3 This is the SEM image of the rare earth and noble metal dual-doped zinc oxide-based photocatalyst material of Example 3 of the present invention DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] Preparation of zinc and rare earth eutectic viscous liquid: first, zinc chloride and lanthanum nitrate hexahydrate are added with an appropriate amount of deionized water to mix into a uniform solution, wherein the molar ratio of zinc chloride to lanthanum nitrate hexahydrate is 1:0.01, and then a mixture of ethylenediaminetetraacetic acid and citric acid in a mass ratio of 2:1 is added as a combined complexing agent, wherein the sum of the mass of zinc chloride and lanthanum nitrate hexahydrate and the mass ratio of the combined complexing agent is 1:0.2, and heated to form a golden and transparent viscous liquid; preparation of a precursor: the viscous liquid is placed in a 250°C oven and heated for 8 hours to form a black precursor; preparation of rare earth element doped zinc oxide: the black precursor is placed in a muffle furnace and calcined at 450°C for 3 hours to form rare earth element doped zinc oxide; preparation of nano Preparation of nanoscale composite dispersion: rare earth element doped zinc oxide, rare earth long-acting luminous powder, dispersant and deionized water are prepared in a nano sand mill to form a nanoscale composite dispersion, and the average particle size is controlled within 50nm, wherein the mass ratio of rare earth element doped zinc oxide to rare earth long-acting luminous powder, dispersant and deionized water is controlled to be 1:0.1:0.3:1; Preparation of composite material filter cake coated with precious metal ions: precious metal silver nitrate is added to the nanoscale composite dispersion, fully dissolved, and then grafted carboxyl starch is added and sheared to form a stable composite solution, wherein the molar ratio of silver nitrate to zinc in the nanoscale composite dispersion is 0.01:1, and the mass ratio of grafted carboxyl starch to the nanoscale composite dispersion is 0.01:1. The filter system is used to filter repeatedly until the filtered clear liquid no longer contains precious metal ions, thereby obtaining a composite material filter cake coated with precious metal ions; preparing a rare earth and precious metal dual-doped zinc oxide-based photocatalyst material: the composite material filter cake coated with precious metal ions is decomposed at a low temperature of 500°C to form a rare earth and precious metal dual-doped zinc oxide-based photocatalyst material in which precious metals are uniformly deposited on the surface of the rare earth / rare earth element doped zinc oxide photocatalyst.
[0030] Example 2
[0031] Preparation of zinc and rare earth eutectic viscous liquid: first, zinc nitrate and scandium nitrate are mixed with an appropriate amount of deionized water to form a uniform solution, wherein the molar ratio of zinc nitrate to scandium nitrate is 1:0.1, and then a mixture of ethylenediaminetetraacetic acid and citric acid in a mass ratio of 2:1 is added as a combined complexing agent, wherein the sum of the masses of zinc chloride and lanthanum nitrate hexahydrate and the mass ratio of the combined complexing agent is 1:0.5, and heated to form a golden and transparent viscous liquid; preparation of a precursor: the viscous liquid is placed in a 250°C oven and heated for 8 hours to form a black precursor; preparation of rare earth element doped zinc oxide: the black precursor is placed in a muffle furnace and calcined at 600°C for 6 hours to form rare earth element doped zinc oxide; preparation of nano-scale composite Dispersion: Rare earth element doped zinc oxide, rare earth long-acting luminous powder, dispersant and deionized water are prepared into a nano-scale composite dispersion in a nano-sand mill, and the average particle size is controlled within 50nm, wherein the mass ratio of rare earth element doped zinc oxide to rare earth long-acting luminous powder, dispersant and deionized water is controlled to be 1:0.1:0.3:2; Preparation of composite material filter cake coated with precious metal ions: Add precious metal ruthenium nitrate to the nano-scale composite dispersion, fully dissolve it, and then add grafted carboxyl starch, shear to form a stable composite solution, wherein the molar ratio of silver nitrate to zinc in the nano-scale composite dispersion is 0.03:1, and the mass ratio of grafted carboxyl starch to the nano-scale composite dispersion is 0.04:1. The filter cake is filtered repeatedly by a filtering system until the filtered clear liquid no longer contains precious metal ions, thereby obtaining a composite material filter cake coated with precious metal ions; a rare earth and precious metal dual-doped zinc oxide-based photocatalyst material is prepared: the composite material filter cake coated with precious metal ions is reduced by a 200°C 5% hydrogen-argon mixed gas to form a rare earth and precious metal dual-doped zinc oxide-based photocatalyst material in which precious metals are uniformly deposited on the surface of the rare earth / rare earth element doped zinc oxide photocatalyst.
[0032] Example 3
[0033] Preparation of zinc and rare earth eutectic viscous liquid: first, zinc nitrate and cerium nitrate hexahydrate are added with an appropriate amount of deionized water to mix into a uniform solution, wherein the molar ratio of zinc nitrate to cerium nitrate hexahydrate is 1:0.2, and then a mixture of ethylenediaminetetraacetic acid and citric acid in a mass ratio of 2:1 is added as a combined complexing agent, wherein the sum of the mass of zinc chloride and lanthanum nitrate hexahydrate and the mass ratio of the combined complexing agent are 1:0.8, and heated to form a golden and transparent viscous liquid; preparation of a precursor: the viscous liquid is placed in a 250°C oven and heated for 8 hours to form a black precursor; preparation of rare earth element doped zinc oxide: the black precursor is placed in a muffle furnace and calcined at 700°C for 8 hours to form rare earth element doped zinc oxide; preparation of nano-scale composite Dispersion: Rare earth element doped zinc oxide, rare earth long-acting luminous powder, dispersant and deionized water are prepared into a nano-scale composite dispersion in a nano-sand mill, and the average particle size is controlled within 50nm, wherein the mass ratio of rare earth element doped zinc oxide to rare earth long-acting luminous powder, dispersant and deionized water is controlled to be 1:0.1:0.3:3; Preparation of composite material filter cake coated with precious metal ions: Add precious metal nitrate or chloride to the nano-scale composite dispersion, fully dissolve it, and then add grafted carboxyl starch, shear to form a stable composite solution, wherein the molar ratio of silver nitrate to zinc in the nano-scale composite dispersion is 0.06:1, and the mass ratio of grafted carboxyl starch to the nano-scale composite dispersion is 0.07:1. The filter is filtered repeatedly through a filtering system until the filtered clear liquid no longer contains precious metal ions, thereby obtaining a composite material filter cake coated with precious metal ions; preparing a rare earth and precious metal dual-doped zinc oxide-based photocatalyst material: the composite material filter cake coated with precious metal ions is reduced by a 250°C 5% hydrogen-argon mixed gas to form a rare earth and precious metal dual-doped zinc oxide-based photocatalyst material in which precious metals are uniformly deposited on the surface of a rare earth / rare earth element doped zinc oxide photocatalyst.
[0034] Example 4
[0035] Preparation of zinc and rare earth eutectic viscous liquid: first, zinc nitrate and yttrium nitrate hexahydrate are added with an appropriate amount of deionized water to mix into a uniform solution, wherein the molar ratio of zinc nitrate to yttrium nitrate hexahydrate is 1:0.33, and then a mixture of ethylenediaminetetraacetic acid and citric acid in a mass ratio of 2:1 is added as a combined complexing agent, wherein the sum of the masses of zinc chloride and lanthanum nitrate hexahydrate and the mass ratio of the combined complexing agent are 1:1, and heated to form a golden and transparent viscous liquid; preparation of a precursor: the viscous liquid is placed in a 250°C oven and heated for 8 hours to form a black precursor; preparation of rare earth element doped zinc oxide: the black precursor is placed in a muffle furnace and calcined at 800°C for 12 hours to form rare earth element doped zinc oxide; preparation of nanoscale complex Composite dispersion: rare earth element doped zinc oxide and rare earth long-acting luminous powder, dispersant and deionized water are prepared into nano-scale composite dispersion in a nano-sand mill, and the average particle size is controlled within 50nm, wherein the mass ratio of rare earth element doped zinc oxide to rare earth long-acting luminous powder, dispersant and deionized water is controlled to be 1:0.1:0.3:4; Preparation of composite material filter cake coated with precious metal ions: precious metal nitrate or chloride is added to the nano-scale composite dispersion, fully dissolved, and then grafted carboxyl starch is added, and sheared to form a stable composite solution, wherein the molar ratio of silver nitrate to zinc in the nano-scale composite dispersion is 0.1:1, and the mass ratio of grafted carboxyl starch to the nano-scale composite dispersion is 0.1:1. The filter cake is filtered repeatedly by a filtering system until the filtered clear liquid no longer contains precious metal ions, thereby obtaining a composite material filter cake coated with precious metal ions; a rare earth and precious metal dual-doped zinc oxide-based photocatalyst material is prepared: the composite material filter cake coated with precious metal ions is reduced by a 300°C 5% hydrogen-argon mixed gas to form a rare earth and precious metal dual-doped zinc oxide-based photocatalyst material in which precious metals are uniformly deposited on the surface of the rare earth / rare earth element doped zinc oxide photocatalyst.
[0036] Comparative Example 1
[0037] The difference from Example 1 is that commercially available nano titanium dioxide photocatalyst from Japan Tayca Company is used.
[0038] Comparative Example 2
[0039] The difference from Example 1 is that a commercially available nano zinc oxide photocatalyst, Zhejiang Huiqian, is used.
[0040] Comparative Example 3
[0041] The difference from Example 1 is that a commercially available nano titanium dioxide photocatalyst / diatomaceous earth composite material, Linjiang Baojian Nano, is used.
[0042] The photocatalysts prepared in Examples 1-4 and Comparative Examples 1-4 of the present application were subjected to performance tests.
[0043] Formaldehyde removal efficiency: Tested in accordance with the test standard QB / T 2761-2006 "Method for determining the purification effect of indoor air purification products" to test the 24-hour formaldehyde removal efficiency
[0044] E. coli antibacterial rate: tested in accordance with the test standard GB / T 30706-2014 "Test method and evaluation of antibacterial performance of photocatalytic antibacterial materials and products under visible light irradiation", and tested the 24-hour E. coli antibacterial rate
[0045] The specific performance test results are shown in Table 1 below:
[0046]
[0047] It can be seen from the results shown in Examples 1-4 and Comparative Examples 1-3 of the present application that the three methods of co-doping with rare earth elements to increase oxygen vacancies, supplementing light in the dark with rare earth long-lasting luminous powder to continue the photocatalytic properties, and physically doping with precious metals to reduce the recombination rate of electron-hole pairs improve the reaction activity and efficiency of the photocatalyst, expand the response range of the photocatalyst to the spectrum, thereby better adapting to visible light and weak light sources, increasing the utilization rate of the light source, and having a stronger removal and killing effect on formaldehyde and E. coli.
[0048] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a rare earth and noble metal dual-doped zinc oxide-based photocatalyst material, characterized in that: The specific steps are as follows: 1) Preparation of zinc and rare earth eutectic viscous liquid: firstly, soluble compounds of zinc and rare earth are mixed into a uniform solution, then a combined complexing agent is added, and heated to form a golden and transparent viscous liquid; 2) Preparing a precursor: placing the viscous liquid in an oven at 250°C and heating it for 8 hours to prepare a black precursor; 3) Preparing rare earth element-doped zinc oxide: placing the black precursor in a muffle furnace and calcining at 450-800° C. for 3-12 hours to prepare rare earth element-doped zinc oxide; 4) preparing a nano-scale composite dispersion: preparing a nano-scale composite dispersion by mixing rare earth element-doped zinc oxide, rare earth long-lasting luminous powder, a dispersant and deionized water in a nano-sand mill, wherein the average particle size is controlled within 50 nm; 5) Preparing a composite material filter cake coated with precious metal ions: adding precious metal nitrate or chloride to the nano-scale composite dispersion, fully dissolving it, then adding grafted carboxyl starch, shearing to form a stable composite solution, and repeatedly filtering through a filtration system until the filtered clear liquid no longer contains precious metal ions, thereby obtaining a composite material filter cake coated with precious metal ions; 6) Preparation of rare earth and precious metal doped zinc oxide-based photocatalyst material: The composite material filter cake coated with precious metal ions is decomposed at 500°C or reduced by 200-300°C 5% hydrogen-argon mixed gas to form a rare earth and precious metal doped zinc oxide-based photocatalyst material in which precious metals are uniformly deposited on the surface of rare earth / rare earth element doped zinc oxide photocatalyst.
2. The method for preparing a rare earth and noble metal dual-doped zinc oxide-based photocatalyst material according to claim 1, characterized in that: The zinc soluble compound in step 1) is one of zinc chloride and zinc nitrate; the soluble compound of the rare earth is a nitrate of the rare earth; the combined complexing agent is a mixture of ethylenediaminetetraacetic acid and citric acid in a mass ratio of 2:1; the rare earth type is one or more of lanthanide elements, scandium and yttrium elements, wherein the lanthanide elements include lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium; the molar ratio of the zinc soluble compound to the rare earth soluble compound is 1:(0.01-0.33), and the mass ratio of the sum of the soluble compound and the rare earth soluble compound to the combined complexing agent is 1:(0.2-1).
3. The method for preparing a rare earth and noble metal dual-doped zinc oxide-based photocatalyst material according to claim 1, characterized in that: In the step 4), the mass ratio of rare earth element-doped zinc oxide to rare earth long-lasting luminous powder, dispersant, and deionized water is controlled to be 1:0.1:0.3:(1-4).
4. The method for preparing a rare earth and noble metal dual-doped zinc oxide-based photocatalyst material according to claim 1, characterized in that: In the step 5), the noble metal nitrate or chloride is one of silver nitrate, platinum nitrate, palladium nitrate, rhodium nitrate, ruthenium nitrate, platinum chloride, palladium chloride, rhodium chloride, and ruthenium chloride, or a combination thereof; the molar ratio of the noble metal to the zinc in the nanoscale composite dispersion is (0.01-0.1):1; and the mass ratio of the grafted carboxyl starch to the nanoscale composite dispersion is (0.01-0.1):1.
Citation Information
Patent Citations
Visible-light-responsive photocatalyst composite material and preparation method thereof
CN112246246A
